The use of e-cigarettes among university students in Malaysia - Wan Puteh, Sharifa Ezat; Abdul Manap, Roslina; Maharani, Hassan; Ahmad, Izzah Syazwani; Idris, Idayu Badilla; Md Sham, Fariza; Yu Lin, Andrea Ban; Soo Chun, Ian; Pakri Mohamad, Mohamed Rashidi; Mokhtar, Ahmad Irdha; Zakaria, Hazli; Lee, Jing; et al. (International Society for the Prevention of Tobacco Induced Diseases, 2018)
INTRODUCTION E-cigarette use is an emerging phenomenon with increasing recognition and acceptance globally. This study aims to create a profile of e-cigarette users among university students in Malaysia. METHODS The study was conducted using a cross-sectional research involving six universities in Malaysia. A semi-structured questionnaire was distributed to 1302 randomly selected students, who either smoked cigarettes and/or e-cigarettes. The 2011 version of Global Adult Tobacco Surveys (GATS) tool was used to record the respondents’ sociodemographic data. RESULTS The study revealed that 74.9% of the respondents smoked e-cigarettes; 40.3% used both cigarettes and e-cigarettes (dual users), and 34.5% were exclusive e-cigarette users. The exclusive use of e-cigarettes was related to gender (OR=0.18, 95% CI: 0.09–0.39). Also, male respondents were the majority users (95%). Of the respondents, 75.2 % were Malays, 98.0% single and most believed they have no health problems (92.1%). Further findings revealed the occurrence of adverse effects, dizziness 14.4%, cough 14.1%, and headaches 12.4%. Overall, 57.8% of the respondents used e-cigarettes as a smoking cessation tool, while others consider e-cigarettes a self-image enhancing tool or as part of social activities. CONCLUSIONS Further research on the use of e-cigarettes should be conducted on a large number of respondents in other settings to augment the findings of this study, and also guide policy making on and prevention practice of e-cigarette use, among the general student population in Malaysia.